The Interaction between Culture and Economy in Vietnam - Uwe Blien; Van Phan thi Hong (European Regional Science Association (ERSA), 2011)
Historically, the Vietnamese state developed in an area along the Red River and within its delta. The need to protect the inhabitants of this land from dangerous floods gave rise to a "hydraulic society", which was accompanied by a specific culture. One of the features of this culture is an emphasis on formal education, which was "inherited" from a past in which the passing of an examination was a precondition for acquiring a high position in the state. Today, the Vietnamese culture is a supporting factor in the current development process in Vietnam. Rigorous reform steps carried out since 1986 have transformed the Vietnamese socialist economy, which mainly followed the Soviet blueprint, into a market driven economy which is governed by strong private incentives. The culture predominant in this country on the one hand supports the functioning of the new capitalist system, and on the other hand compensates for many of its weaknesses. As a consequence a development process has been generated which has led to high rates of economic growth. However, it is not without systemic risks.
Keywords: 330